Mechanisms by which oxygen acts as a surfactant in giant magnetoresistance film growth - Larson, D; Petford-Long, A; Cerezo, A; Bozeman, S; Morrone, A; Ma, Y; Georgalakis, A; Clifton, P (2003)
The mechanisms by which oxygen acts as a surfactant in giant magnetoresistance multilayers have been elucidated for the first time. Three-dimensional atom probe analysis of Cu/CoFe multilayers reveals the elemental distributions at the atomic level. Interfacial intermixing and oxygen impurity levels have been quantified for the first time. Both with and without oxygen the intermixing is greater at the CoFe-on-Cu interface than at the Cu-on-CoFe one and for both interfaces, oxygen reduced the intermixing. The oxygen largely floats to the growing surface and is incorporated at grain boundaries. The oxygen also reduces conformal roughness and grain boundary grooving, indicating a reduction in long-range surface diffusion.